BUSINESS DEVELOPMENT THROUGH A BUSINESS MODEL CANVAS APPROACH AT ELFATH MSMES - Erika Luthfi Afifah; Ito Setiawan (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
Elfath UMKM is one of the UMKM in Purbalingga Regency, Central Java, which is located in Kaligondang Village. This UMKM is engaged in the production of snacks in the form of macaroni cheese. Based on the potential for product sales and also the number of MSMEs engaged in the production sector, the competition between fields is getting tighter. The problem with Elfath's MSMEs is that the business model has not been maximally implemented. So that the Elfath MSME needs to develop an ongoing business model so that later it can compete with other MSMEs. This study aims to identify the business model that is currently running in Elfath MSMEs and to develop a business model for Elfath MSMEs with a Business Model Canvas (BMC) approach and SWOT analysis. By using the BMC method, it can provide greater business opportunities by developing business models, while the SWOT analysis is used to determine the strengths, weaknesses, opportunities, and threats to these SMEs. The results of the study show that the business model currently being run by Elfath SMEs has fulfilled the 9 elements of the Business Model Canvas. Even though it has fulfilled the 9 elements of BMC, Elfath SMEs need to develop the business model by maximizing the strategies contained in the 9 elements of BMC through SWOT analysis.